KINERJA DINAS KOPERASI DAN UMKM - Meyzi Heriyanto, Syahirul Alim, Zaili Rusli, (Jurnal Ilmu Administrasi Negara, 2019)
Performance of Cooperative and UMKM Offices. This study aims to analyze howmuch the performance of the Employees of the Pekanbaru City Cooperative and SMEs Office infostering cooperatives in the administrative area of Pekanbaru Municipality. This research isqualitative. Data collection was carried out by library research and field research usingobservations and interviews. The data will then be analyzed qualitatively. With a population of 40people used as respondents. The research informants were the Lurah, the Head of the Office,LKMD and RW. Based on the results of research conducted, it can be concluded that employeeperformance is influenced by individual factors related to the background and experience ofemployees, psychological factors that include employee attitudes towards cooperative problemsthat exist and organizational factors that awaken the hierarchical system of the service so that thereis awareness in the main tasks and the function of each field The performance of the UMKMCooperative Office in Pekanbaru City in 2014 had a positive impact on the development ofcooperatives in Pekanbaru City. The State Civil Society must be aware of their duties and roles inpublic service to the community in the field of Cooperatives and MSMEs in Pekanbaru City sothat employee performance will increase the growth of cooperatives and new entrepreneurs isincreasing rapidly.